Carbon and nitrogen cycling on the Qinghai-Tibetan Plateau - Chen, Huai; Ju, Peijun; Zhu, Qiuan; Xu, Xingliang; Wu, Ning; Gao, Yongheng; Feng, Xiaojuan; Tian, Jianqing; Niu, Shuli; Zhang, Yangjian; Peng, Changhui; Wang, Yanfen (Nature Reviews Earth & Environment, 2022)
The Qinghai-Tibetan Plateau (QTP) has experienced atmospheric warming, cryosphere thaw and intensified human activities since the 1970s. These changes have had sometimes striking impacts on the hydrology, ecosystems and biogeochemistry of the region. In this Review, we describe carbon and nitrogen cycling on the QTP. Overall, the QTP has been a net carbon sink (with a net carbon balance of similar to 44 million tons of carbon uptake peryear) and a methane source (similar to 0.96 trillion grams per year of carbon in the form of methane, TgCH(4)-Cyr(-1)) since the 2000s. Rising temperatures, precipitation and nitrogen availability drive primary productivity increases, leading to increased carbon uptake. Conversely, these factors also increase greenhouse gas emissions, soil respiration rates and permafrost carbon mobilization, increasing carbon loss. Anthropogenic activities such as overgrazing and construction decrease plant production and soil carbon and nitrogen stocks, but restoration efforts on the QTP drive regional increases in these stocks. On balance, these changes are complex but largely offset each other. In the future, the QTP is predicted to still function as a net carbon sink, despite ongoing severe permafrost degradation. Moreover, nitrogen stocks are expected to remain relatively stable, partly related to potential future decreases in nitrogen deposition.